The Kaali crater field and other geosites of Saaremaa Island (Estonia): the perspectives for a geopark - Raukas, Anto; Stankowski, Wojciech (Bogucki Wydawnictwo Naukowe, 2010)
The Island of Saaremaa in Estonia offers highly spectacular geological features that belong to the most interesting in the Baltic Sea area. A unique geological monument on the island is the Kaali meteorite–crater field, formed by nine meteorite impacts. There are also attractive coastal cliffs, huge erratics, alvars (limestone areas covered by a very thin soil) and well-developed glacial and marine landforms. Limestone cliffs and shingle beaches abound with Silurian fossils and offer great opportunities to fossil collectors. The island is a prospective geopark. During the past few years, the geology of the island has become an intensely studied object of Estonian and Polish geologists.
Keywords: Geopark; Geosites; Meteorite–crater field; Saaremaa Island; Estonia